Lexical density and variation in Indonesian folklores in English student textbooks: an SFL study - Eva Tuckyta Sari Sujatna; H Heriyanto; Setiadi Andri (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2021)
This study aims to study the lexical density and lexical variation in Indonesian folklore narrative texts in English textbooks for grade X which were published by the Ministry of Education and Culture of The Republic of Indonesia. This study uses qualitative method since this study focuses on lexical density and lexical variation in the texts from the textbooks. This study applies the theory of Systemic Functional Linguistics based on lexical density theory of Ure (1971) which was refined by Halliday (1985) and the theory of lexical variation of Castello (2008). In addition, Gunning Fog Index and Estimated Reading Grades by Heydari (2012) are also applied to help measure suggested reading grades of the texts. The data are three narrative texts about Indonesian folklore from Bahasa Inggris: third edition (2017) and Interlanguage (2008) textbooks. This study revealed that the texts vary in terms of their lexical density and lexical variation. Moreover, in some of the texts, their lexical variation does not go in line with their lexical density and affect the difficulty level of the texts to be comprehended. This study also revealed that the texts vary in terms of Gunning Fog Index and many of the texts are suggested for lower graders.